FRIED'S PHENOTYPE: FRAILTY INCIDENCE AMONG ELDERLY PEOPLE IN A FAMILY HEALTH UNIT (Fiep Bulletin - online, 2014)
Objective: determine the frailty syndrome incidence among elderly people, according to Fried's Phenotype, in a Family Health unit. Methodology: exploratory study, with a quantitative approach, carried out in a Family Health unit in the town of Cajazeiras, Paraíba, Brazil. Data were collected in the unity “João Bosco Braga Barreto” in April and May 2013, after approval by the Research Ethics Committee of Faculdade Santa Maria, under the Protocol 240,731. The sample consisted of 100 elderly people. We used a sociodemographic questionnaire and the Fried's Phenotype markers were statistically analyzed using the software PASW, version 20. Results: 52% of participants were classified as pre-frail and 48% were classified as frail. Conclusion: we found out a relatively equitable division between the frailty and pre-frailty frequencies, in addition to a relation to sex and body mass index. We indicate the importance of investing in health policies to minimize the frailty syndrome prevalence among elderly people.
Keywords: Demographic aging; Elderly person; Fried's phenotype; Family Health Unity.